An ultra-effective method of generating extramultipotent cells from human fibroblasts by ultrasound. (October 2017) - Lee, Yong Seung; Heo, Hyejung; Lee, Jonghwan; Moon, Sung Ung; Jung, Woon Yong; Park, Yong Keun; Park, Min Geun; Oh, Seung-Hun; Kim, Soonhag
Abstract: Multipotent cells have similar basic features of all stem cells but limitation in ability of self-renewal and differentiation compared with pluripotent cells. Here, we have developed an ultra effective, gene- and chemical-free method of generating extra multipotent (xpotent) cells which have differentiation potential more than limited cell types, by the mechanism of ultrasound-directed permeation of environmental transition-guided cellular reprogramming (Entr). Ultrasound stimulus generated a massive number of Entr-mediated xpotent (x/Entr) spheroids from human dermal fibroblasts (HDFs) 6 days after treatment. The emergence of x/Entr was first initiated by the introduction of human embryonic stem cell (ESC) environments into the HDFs to start fast cellular reprogramming including activation of stress-related kinase signaling pathways, subsequent chromatin remodeling, and expression of pluripotent-related genes via transient membrane damage caused by ultrasound-induced cavitation. And then, pluripotent markers were transported into their adjacent HDFs via direct cell-to-cell connections in order to generate xpotent clusters. The features of x/Entr cells were intermediate between pluripotency and multipotency in terms of pluripotency with three germ layer markers, multi-lineage differentiation potential, and no teratoma formation. This physical stimulus-mediated reprogramming strategy was cost-effective, simple, quick, produced significant yields, and was safe, and can therefore provide a new paradigm for clinical application.